How AI is used in FDA-authorized medical devices: a taxonomy across 1,016 authorizations - Rohan Singh; Monika Bapna; Abdul Rahman Diab; Emily S. Ruiz; William Lotter (npj Digital Medicine)
Abstract We reviewed 1016 FDA authorizations of AI/ML-enabled medical devices to develop a taxonomy capturing key variations in clinical and AI-related features. Quantitative image analysis remains the most common application, but its relative proportion has declined recently. Over 100 devices leverage AI for data generation, though none yet involve LLMs. Our taxonomy clarifies current AI usage in medical devices and provides a foundation for tracking developments as applications evolve.